(untitled) (The Nepali Mathematical Sciences Report, 2016)
Conduction-radiation heat transfer problem is usually formulated with a highly nonlinear integrodifferential equation. In this paper we describe a simple technique for modeling radiation heat transfer in a semi-transparent medium with arbitrary varying spectral absorption coefficient and purpose a computational model (described by a coupled system of elliptic-parabolic PDEs) based on flux limited diffusion theory. Numerical simulations of a glass cooling problem in one dimension show that the proposed method is comparable to a higher order discrete ordinate (S8) method.